Strategic approach to enhance the marketability of insurance products for Maybank / Mohd Shafie Md Sarip, Norliza Miswan and Rafidah Abd Azis (Faculty of Business and Management, 2008)
This research is being done in order to determine the strategic approach to enhance the marketability of life insurance product for Maybank. As the financial landscape in Malaysia had undergone tremendous transformation in the last decade. The evolution in the financial landscape saw a shift in customers' preference, emergence of more complex products and increasing diversity in delivery channels (Mohd. Razif, 2007). In today's world of economic growth, people hardly can live without insurance. Insurance is a boon to the mankind in several ways. There are a wide range of insurance policies like the health and the property insurance.